β-glucan attenuates intestinal ischemia-reperfusion injury in mice by promoting glucagon-like peptide-1 secretion - WANG Wei; HAN Ben; SUN Lihua (陆军军医大学学报)
Objective‍　‍To investigate the protective effect of β-glucan (BG) against intestinal ischemia reperfusion (II/R) injury by regulating the secretion of glucagon-like peptide-1 (GLP-1). Methods‍　‍Male C57BL/6 mice (6~8 weeks old) were subjected, and finally, the experiments had sham group, II/R group, II/R+BG group (0.1 mg/mL BG in drinking water for 2 weeks before modeling), II/R+liraglutide (LLT, GLP-1 analogue) group (0.2 μg/g LLT injected every 12 hours for 3 consecutive days before modeling), and II/R+BG+Ex9-39 (GLP-1R antagonist) group (intraperitoneal injection of 2 μg/g Ex9-39 1 h before modeling). After modeling, HE staining was used to observe intestinal morphological changes, and RT-qPCR and Western blotting were employed to evaluate the molecules (Occludin, ZO-1 and Claudin-1) related to intestinal barrier damage. The effect of 0.1 mg/mL BG treatment on the GLP-1 level in the serum and intestinal tissues of normal mice was determined with ELISA and immunofluorescence assay, respectively, and RT-PCR for the molecules related to GLP-1 expression (Gcg, Pcsk1/2, GIP and Foxa2). The effects of LLT and Ex9-39 pretreatment on intestinal morphology and intestinal barrier damage were also determined by morphological observation and expression levels of related molecules. Results‍　‍II/R induced significant decreases in the mRNA levels of Occludin, ZO-1 and Claudin-1 and increase in Chiu's score when compared with sham control mice (P<0.05). While, the mRNA levels of the 3 molecules were obviously higher and the Chiu's score was lower in the II/R+BG group than the II/R group (P<0.05). BG pretreatment induced notably enhanced secretion of GLP-1 in the serum and intestinal tract of normal mice, and improved the mRNA expression of GLP-1-related molecules (P<0.05). The intervention of GLP-1 analogue LLT could attenuate the II/R damage and decreased Chiu's score, with statistical difference in comparison with the II/R group (P<0.05). GLP-1 receptor antagonist Ex9-39 reversed the protective effects of BG pretreatment against II/R damage, with notably differences in the expression of Occludin, ZO-1 and Claudin-1 and Chiu's score (P<0.05). Conclusion‍　‍BG can attenuate intestinal mucosal and functional injury after II/R by promoting intestinal GLP-1 secretion.